2015
DOI: 10.1128/jvi.00039-15
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mutations Enhance Assembly and Cell-to-Cell Transmission of a High-Titer Hepatitis C Virus Genotype 5a Core-NS2 JFH1-Based Recombinant

Abstract: Recombinant hepatitis C virus (HCV) clones propagated in human hepatoma cell cultures yield relatively low infectivity titers. Here, we adapted the JFH1-based Core-NS2 recombinant SA13/JFH1 C3405G,A3696G (termed SA13/JFH1 orig ), of the poorly characterized genotype 5a, to Huh7.5 cells, yielding a virus with greatly improved spread kinetics and an infectivity titer of 6.7 log 10 focus-forming units (FFU)/ml. We identified several putative adaptive amino acid changes. In head-to-head infections at fixed multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 83 publications
(186 reference statements)
4
49
1
Order By: Relevance
“…In general, our data do not support the concept of virion assembly-independent HCV transmission. In agreement with our findings, adaptive assembly-enhancing mutations conferred significantly increased cell-to-cell transmission (41).…”
Section: Discussionsupporting
confidence: 82%
“…In general, our data do not support the concept of virion assembly-independent HCV transmission. In agreement with our findings, adaptive assembly-enhancing mutations conferred significantly increased cell-to-cell transmission (41).…”
Section: Discussionsupporting
confidence: 82%
“…However, viral escape mutants are generally difficult to generate with HCVcc because of the inherently high antibody resistance of most HCV isolates. In addition, we have shown that the high fitness of certain viruses, like core-NS2 recombinants J6/JFH1 and SA13/JFH1, permits the viruses to spread in culture, even at high concentrations of antibody, without developing resistance substitutions (24,31), possibly aided by high levels of cell-to-cell spread (32,33). Previously, we studied AR5A resistance by using novel HCVcc with a deletion of hypervariable region 1 (HVR1) (24).…”
mentioning
confidence: 99%
“…These HCVcc have been used to further define viral entry pathways (Brimacombe et al, 2011;Carlsen et al, 2013;Mathiesen et al, 2015;Timpe et al, 2008) and to show that broadly neutralizing monoclonal antibodies (bNAbs) can prevent HCV infection in animal models (Forns et al, 2000;Morin et al, 2012;Youn et al, 2005). Panels of HCVcc expressing E1E2 from multiple genotypes have also been used to measure neutralizing breadth of bNAbs (Carlsen et al, 2014;Keck et al, 2008Keck et al, , 2013Law et al, 2008).…”
Section: Introductionmentioning
confidence: 99%